Community Development Model by Corporate Social Responsibility in Indonesia: A Systematic Literature Review - Widhagdha, Miftah Faridl; Santosa, Fajar Julian; Wardani, Raden Roro Ilma Kusuma; Retnaningsih, Triya Ayu; Kartono, Drajat Tri (Indonesian Social Work Consortium (ISWC), 2022)
Community empowerment is one form of implementation of corporate social responsibility (CSR) carried out by companies. In its implementation, there are various models and strategies that can be used to support implementation. In Indonesia, the study of community empowerment by companies has become a new tradition in the development of CSR models. In the last decade, various models of community empowerment by companies have developed resulting from research related to CSR, especially those that examine community empowerment. This research is a systematic literature review to analyze the model of community empowerment by companies that are reviewed based on dissertation research sources published in the 2013-2020 period by Sebelas Maret University. There are 9 dissertation studies that were analyzed to find a synthesis of community empowerment models in corporate social responsibility programs. The majority of the studies were conducted in case studies with a qualitative approach. The findings of this study are that the model of community empowerment by companies in Indonesia is developed based on the “local context” and “actor relations” that exist within the scope of the community empowerment program.